Survival Rate of Endodontically Treated Teeth Restored with Different Post and Core Systems - Halli, Basavaraj; Janavathi, Janavathi; shaik, Jaheer; penumaka, Ramesh; Kumar, Konagala Ravi; pradeep, Buggaveeti (Journal of Neonatal Surgery, 2025)
Background: The longevity and success of endodontically treated teeth (ETTs) are largely influenced by the type of post and core systems used for their restoration. Different post and core materials and techniques have been proposed to improve the retention, strength, and functional outcome of ETTs. This study evaluates the survival rate of ETTs restored with different post and core systems. Objectives: To compare the survival rate of endodontically treated teeth restored with various post and core systems. Methods: A total of 120 ETTs were selected from patients at a dental clinic and divided into four groups based on the type of post and core system used. The systems were: Group 1 (metal post and core), Group 2 (fiber-reinforced composite post and core), Group 3 (ceramic post and core), and Group 4 (resilon post and core). Teeth were monitored for 2 years post-treatment, with regular follow-ups at 6, 12, and 24 months. Clinical outcomes, including failure, fracture, and dislodgement, were recorded. Results: The survival rate was highest in the fiber-reinforced composite post group (95%), followed by the ceramic post group (90%), the metal post group (85%), and the resilon post group (80%). Statistical analysis indicated significant differences between groups (p < 0.05). Conclusion: Fiber-reinforced composite posts provided the highest survival rate for ETTs, followed by ceramic and metal posts. Resilon posts demonstrated the lowest survival rate, suggesting that material choice plays a crucial role in the longevity of endodontically treated teeth.